L’approche variationnelle de la rupture : un exemple de collaboration fructueuse entre mécaniciens et mathématiciens - Marigo, Jean-Jacques (Comptes Rendus. Mécanique)
This article reviews some important steps in the development and application of the variational approach to fracture. It emphasizes the essential role played by the permanent dialogue between mechanicians and applied mathematicians in bringing about this new paradigm and ensuring its undeniable success.